Joint impacts of relaying scheme and wireless power transfer in multiple access of cellular networks - Anh-Tu Le; Dinh-Thuan Do (Institute of Advanced Engineering and Science, 2021)
This paper considers ergodic capacity of energy harvesting (EH) based cellular networks. Such a network employs non-orthogonal multiple access (NOMA) together with relaying scheme to serve two far users. In this system model, relay is facilitated power splitting (PS) protocol to implement energy harvesting (EH). To examine capacity, expressions of signal to noise ratio (SNR) need be computed to achieve capacity. Power allocation factors are different for two users in such system and hence performance gap happens to distinguish requirements for separated users. It can be confirmed that the proposed paradigm exhibits maximal achievable capacity in some scenarios of setting parameters. To confirm exactness of the analytical expressions and show advantages of the proposed EH-NOMA, simulation results are performed in terms of ergodic capacity.